A Generic Approach for Analysis of White-Light Interferometry Data via User-Defined Algorithms. - Schneider, Max; Fey, Dietmar; et al. (Computational Science and Its Applications - ICCSA 2014, 2014)
The non-destructive and automatic 3D surface analysis using white-light interferometry has very high demands on the required computing systems. This is due to both, the high volume of data that are collected and the tremendous computational power, required by algorithms which evaluate the data. Furthermore, material characteristics and environmental influences like temperature or ambient light have a not negligible effect on the scan procedure, such that the algorithmic approaches must be adjusted to assess the correct surface profile. Thus, to obtain the desired analysis results and to fulfill the computational requirements, the application developer has to consider the physical characteristics of the white-light interferometry process as well as the attributes of the computational platform used. This paper describes the generic computational module of a new framework for the white-light interferometry surface scanning procedure to address these problems. This framework allows a user-transparent automatic assessment and usage of available computational resources. © 2014 Springer International Publishing.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD3.agener
Keywords: Function objects; Generic algorithms; GPGPU; High-performance computing; White-light interferometry